Experiences of donor conception : parents, offspring, and donors through the years - Lorbach, Caroline, 1956- (Jessica Kingsley Publishers, 2003)
Annotation "Drawing on the experiences of parents, offspring and donors and including her own and her family's story, this thought-provoking and informative book explores the process of donor conception. From finding out about an infertility problem, to considering whether - and how - to tell the children about their conception, and how those children feel as the adult offspring of a donor, she provides practical suggestions as well as in-depth consideration of the emotional and ethical issues involved." "Lorbach takes the reader step-by-step through the process of deciding to use donor conception, choosing a donor, and discussing the decision with others and considers the perspective of the donor alongside those of parents and offspring. Tackling difficult subjects such as disclosure and offspring's access to information about the donor, this important book is a much-needed resource for health, counseling and social work professionals as well as for the couples and families themselves."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved